TELAAH PENGARUH PEMIKIRAN TAFSIR FEMINISME AMINA WADUD TERHADAP MASYARAKAT MUSLIM BARAT - Andi Amirah Farhana Hanna; Syarif Abbas Abbas (EL-ADABI : Jurnal Studi Islam, 2023)
Since before Islam arrived in Arab landsl until now it has spread throughout the world, gender injustice still occurs, men often marginalize women, especially in terms of leadership. Amina Wadud Muhsin feels a patriarchal feeling from the phenomenon of Muslim society that occurs. Amina resolved that the problem was contrary to the message of the Koran which brings justice to all mankind regardless of gender. This assumption stems from his concern that interpretations are carried out by men without the participation and views of women, eventually leading to interpretations that are detrimental to women. From this concern then mad e Amina Wadud fight for women's rights through the feminist movement she was carrying. The research method used is qualitative with sources to the recognition of libraries taken from books, journals and other scientific works. The form of research is character research by studying the thoughts of feminist figures Amina Wadud Muhsin and their influence on Western Muslim society. The results of this study then found that Amina Wadud's breakthrough feminist thinking influenced the thoughts of Muslim women in Western countries. This can be seen from the change in their mindset which no longer wants to just follow or be controlled by men. Feminism fighters carried out many reforms such as the emergence of Lady Imam which was pioneered by Amina Wadud with mixed congregations of men and women on the grounds that women can also be leaders like men (gender equality), they believe that that is the message of justice brought down by al -Quran. Western Muslim women began to lead prayer/worship rituals which were generally carried out by men.